2018
DOI: 10.1002/bdr2.1390
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart disease complexity and childhood cancer risk

Abstract: Background: Childhood cancer is increased in those with birth defects, including those with congenital heart disease (CHD). Lymphoma risk is increased in children with CHD. This study analyzes the effect of CHD and CHD severity on childhood cancer risk. Methods: We analyzed cancer risk in a population-based cohort of children with and without CHD born between 1988 and 2004 by linking data from the California Birth Defects Monitoring Program with data from the California Cancer Registry. We compared cancer risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
3
23
1
Order By: Relevance
“…15 Two other studies have shown a 28%-45% increased cancer risk among children with CHDs. 28,30 Our findings on positive associations between pediatric cancers and gastrointestinal defects are consistent with a previous study by Fisher and colleagues, in which a statistically significant association (HR 2.44) was observed between birth defects of the digestive system and pediatric cancers. 15 We also observed increased risk for sarcomas from ages 5-9 (HR 3.9; 95% CI 1.4-11.0).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…15 Two other studies have shown a 28%-45% increased cancer risk among children with CHDs. 28,30 Our findings on positive associations between pediatric cancers and gastrointestinal defects are consistent with a previous study by Fisher and colleagues, in which a statistically significant association (HR 2.44) was observed between birth defects of the digestive system and pediatric cancers. 15 We also observed increased risk for sarcomas from ages 5-9 (HR 3.9; 95% CI 1.4-11.0).…”
Section: Discussionsupporting
confidence: 92%
“…[13][14][15][16][17] Similar to these studies, our study confirms the strong association between cardiovascular defects and neoplasms in early childhood, especially during first year of life. 28,29 After excluding children with chromosomal birth defects or leukemia, Fisher and colleagues found more than a three-fold risk of cancer in children with CHDs. 15 Two other studies have shown a 28%-45% increased cancer risk among children with CHDs.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer have presented data on the distribution of cancer diagnoses in children with birth defects. Collins et al 23 reported a lower relative frequency of leukemia in children with congenital heart disease in comparison with children without it (28% vs 36%) and a higher relative frequency of neuroblastoma (9.0% vs 6.7%). Wong‐Siegel et al 13 reported larger proportions of central and peripheral nervous system tumors, soft‐tissue sarcomas, and renal tumors in pediatric cancer patients with birth defects in comparison with those without birth defects.…”
Section: Discussionmentioning
confidence: 98%
“…Congenital heart disease (CHD) affects approximately 1 in 100 live births [ 61 ], and children with CHD have a higher rate of childhood cancer than individuals born without CHD [ 62 ]. Leukemia and lymphoma are the most common pediatric cancers observed in children with CHD, each accounting for approximately 28% of cases [ 62 ].…”
Section: Pediatric Cardio-oncology Healthcare Modelmentioning
confidence: 99%
“…Congenital heart disease (CHD) affects approximately 1 in 100 live births [ 61 ], and children with CHD have a higher rate of childhood cancer than individuals born without CHD [ 62 ]. Leukemia and lymphoma are the most common pediatric cancers observed in children with CHD, each accounting for approximately 28% of cases [ 62 ]. For instance, an estimated 40–60% of patients with trisomy 21 harbor CHD, and this group is at increased risk for developing transient myeloproliferative disorder (exclusively seen in patients with Down syndrome), acute megakaryoblastic leukemia (500-fold), and acute lymphoblastic leukemia (10- to 20-fold) compared to the non-Down syndrome population [ 63 , 64 , 65 ].…”
Section: Pediatric Cardio-oncology Healthcare Modelmentioning
confidence: 99%